Probiotics mitigate thermal stress- and pathogen-driven impacts on coral skeleton - Mahdi Moradi; Phillipe R. Magalhaes; Raquel S. Peixoto; Cassia C.A.C. Jonck; Daniel François; Anna Clara F. Bellot; Jonatã B. Teixeira; Carla S. Silveira; Gustavo Duarte; Heitor Evangelista; Catia F. Barbosa (Frontiers in Marine Science, 2023)
Threats leading to a reduction in coral populations are apparent worldwide. Several different approaches have been tested to accelerate the adaptation of corals to a changing climate. Here, we evaluated the skeleton structure, crystal habit, and chemical changes of the coral Pocillopora damicornis in response to the pathogen ( Vibrio coralliilyticus ) and probiotic (Beneficial Microorganisms for Corals, BMCs) inoculation under ambient conditions (26 °C) and thermal stress (30 °C) during a 50-day mesocosm experiment. The skeletons were analyzed using microtomography, energy-dispersive x-ray spectroscopy (EDX/SEM), and densitometry to investigate the skeleto-physico-chemical micro-morphological changes in porosity, median pore-size diameter, crystal habit, Mg/Ca, Sr/Ca, the skeleton mineral density (g/cm 2 ) and skeleton mineral content (g –2 ). The results indicate considerable changes in the coral skeleton caused by both temperature and microbial inoculation. Most importantly, lower density (to ∼ x̄ 0.5 g/cm 2 ) and higher porosity (up to ∼ x̄ 47%) were correlated with inoculation of V. coralliilyticus and mitigated by probiotics. BMCs also substantially increased calcification, as evidenced by Mg/Ca in the skeleton of thermally stressed corals. At the micron scale, aragonite crystal fibbers precipitated during the experiments showed an acicular habit in thermally stressed and pathogen-inoculated corals kept at 30 °C. In contrast, a spherulitic habit, characteristic of high growth rates, was observed in corals inoculated with both BMCs and V. coralliilyticus . Our findings reveal that pathogen inoculation and thermal stress had notable impacts on coral skeleton properties, including porosity, density, and crystal morphology, in a short period of time, which highlights the potential impacts of shifts in climate warming and environmental quality. Interestingly, BMCs played a role in maintaining the properties of skeleton calcification.